Urinary Sodium and Potassium Excretion and Risk of Chronic Kidney Disease Progression. (June 2015) - He, Jiang; Mills, Katherine T.; Appel, Lawrence J.; Chen, Jing; Lee, Belinda T.; Hamm, L. Lee; Kusek, John W.
Abstract : Background: Chronic kidney disease (CKD) is a major risk factor for end-stage renal disease, cardiovascular disease, and premature death. Objective: We studied the association of urinary sodium and potassium excretion with CKD progression and all-cause mortality. Method: The Chronic Renal Insufficiency Cohort Study is a multicenter prospective cohort study of 3, 939 patients with CKD in the US. Urinary excretion of sodium and potassium was measured using three 24-hour urine specimens and calibrated to gender-specific mean creatinine excretion. CKD progression was defined as a composite endpoint of incident end-stage renal disease or halving of estimated-glomerular filtration rate from baseline. Result: A total of 905 CKD progression events and 540 deaths from all-causes were identified during follow-up. Compared to those with urinary sodium excretion in the lowest quartile (<125.9 mmol/24 hours), hazard ratios (95% confidence intervals) for the study participants with urinary sodium excretion in the highest quartile (≥197.8 mmol/24-hours) were 1.53 (1.25, 1.86) for CKD progression and 1.60 (1.23, 2.07) for all-cause mortality after adjustment for important co-variables. Likewise, compared to those with urinary potassium excretion in the lowest quartile (<41.3 mmol/24 hours), hazard ratios (95% confidence intervals) for the study participants with urinary potassium excretion in the highest quartile (≥70.6 mmol/24-hours) were 1.94 (1.55, 2.44) for CKD progression and 1.27 (0.94, 1.71) for all-cause mortality. Conclusion: These results indicate that both high urinary sodium and potassium excretion are associated with increased risk of kidney disease progression in patients with CKD.